Cho \(\tan \frac{\alpha }{2} = - 2\). Tính \(\tan \alpha \)
Cho \(\tan \alpha = \frac{2}{3}\) với \(\pi < \alpha < \frac{{3\pi }}{2}\). Tính \(\cos \alpha \) và \(\sin \alpha \)
Ta có:
\(\begin{array}{l}{\tan ^2}\alpha + 1 = \frac{1}{{{{\cos }^2}\alpha }}\\ \Rightarrow {\left( {\frac{2}{3}} \right)^2} + 1 = \frac{1}{{{{\cos }^2}\alpha }}\\ \Rightarrow \frac{1}{{{{\cos }^2}\alpha }} = \frac{{13}}{9}\\ \Rightarrow \cos \alpha = \pm \frac{{3\sqrt {13} }}{{13}}\end{array}\)
Do \(\pi < \alpha < \frac{{3\pi }}{2} \Rightarrow \cos \alpha = - \frac{{3\sqrt {13} }}{{13}}\)
Ta có: \(\begin{array}{l}\tan \alpha = \frac{{\sin \alpha }}{{\cos \alpha }} \Rightarrow \frac{2}{3} = \sin \alpha :\left( { - \frac{{3\sqrt {13} }}{{13}}} \right)\\ \Rightarrow \sin \alpha = - \frac{{2\sqrt {13} }}{{13}}\end{array}\)
Cho biết \(\cos\alpha=-\frac{2}{3}\)
Tính \(A=\frac{\cot\alpha+2\tan\alpha}{2\cot\alpha+\tan\alpha}\)
hh
Cho tan\(\alpha\) + cot\(\alpha\) = 2
a, Tính cos\(\alpha\), sin\(\alpha\), tan\(\alpha\), cot\(\alpha\).
b, Tính E = \(\dfrac{sin\alpha.cos\alpha}{tan^2\alpha+cot^2\alpha}\)
Lời giải:
a.
$\tan a+\cot a=2\Leftrightarrow \tan a+\frac{1}{\tan a}=2$
$\Leftrightarrow \frac{\tan ^2a+1}{\tan a}=2$
$\Leftrightarrow \tan ^2a-2\tan a+1=0$
$\Leftrightarrow (\tan a-1)^2=0\Rightarrow \tan a=1$
$\cot a=\frac{1}{\tan a}=1$
$1=\tan a=\frac{\cos a}{\sin a}\Rightarrow \cos a=\sin a$
Mà $\cos ^2a+\sin ^2a=1$
$\Rightarrow \cos a=\sin a=\pm \frac{1}{\sqrt{2}}$
b.
Vì $\sin a=\cos a=\pm \frac{1}{\sqrt{2}}$
$\Rightarrow \sin a\cos a=\frac{1}{2}$
$E=\frac{\sin a.\cos a}{\tan ^2a+\cot ^2a}=\frac{\frac{1}{2}}{1+1}=\frac{1}{4}$
Cho \(\tan\alpha-5\cot\alpha+4=0.\). Tính \(A=\frac{4\sin\alpha+2\cos\alpha}{3\sin\alpha-\cos\alpha}\)
\(tana-5cota+4=0\Rightarrow tana-\dfrac{5}{tana}+4=0\)
\(\Rightarrow tan^2a+4tana-5=0\Rightarrow\left[{}\begin{matrix}tana=1\\tana=-5\end{matrix}\right.\)
\(A=\dfrac{4sina+2cosa}{3sina-cosa}=\dfrac{\dfrac{4sina}{cosa}+\dfrac{2cosa}{cosa}}{\dfrac{3sina}{cosa}-\dfrac{cosa}{cosa}}=\dfrac{4tana+2}{3tana-1}=\left[{}\begin{matrix}3\\\dfrac{9}{8}\end{matrix}\right.\)
Chứng minh các hệ thức sau:
a) \(\frac{1-cos\alpha}{sin\alpha}=\frac{sin\alpha}{1+cos\alpha}\)
b) \(tan^2\alpha-sin^2\alpha=tan^2\alpha.sin^2\alpha\)
c) \(\frac{1-tan\alpha}{1+tan\alpha}=\frac{cos\alpha-sin\alpha}{cos\alpha+sin\alpha}\)
a) \(\frac{1-\cos\alpha}{\sin\alpha}=\frac{\sin\alpha}{1+\cos a}\)
\(\Leftrightarrow\left(1-\cos\alpha\right)\left(1+\cos\alpha\right)=\sin^2\alpha\)
\(\Leftrightarrow1-\cos^2\alpha=\sin^2\alpha\)
\(\Leftrightarrow\sin^2\alpha+\cos^2\alpha=1\)( luôn đúng )
\(\Rightarrow\frac{1-\cos\alpha}{\sin\alpha}=\frac{\sin\alpha}{1+\cos\alpha}\)
CMR
a)\(\frac{1+\cos\alpha}{\sin\alpha}=\frac{\sin\alpha}{1-\cos\alpha}\)
b)\(\frac{\tan\alpha+1}{\tan\alpha-1}=\frac{1+\cot\alpha}{1-\cot\alpha}\)
c) \(\tan^2\alpha-\sin^2\alpha=\tan^2\alpha.\sin^2\alpha\)
d)\(\frac{1-4\sin^2\alpha.\cos^2\alpha}{\left(\sin\alpha-\cos\alpha\right)^2}=\left(\sin\alpha+\cos\alpha\right)^2\)
Cho tanα - cotα =3. Tinh gtri bthuc \(\frac{1}{tan^2\alpha}+\frac{1}{cot^2\alpha}\)
\(tana-cota=3\Rightarrow\left(tana-cota\right)^2=9\)
\(\Rightarrow tan^2a+cot^2a-2=9\Rightarrow tan^2a+cot^2a=11\)
\(\frac{1}{tan^2a}+\frac{1}{cot^2a}=\frac{tan^2a+cot^2a}{\left(tana.cota\right)^2}=tan^2a+cot^2a=11\)
Cho góc \(\alpha\) thỏa mãn : \(\frac{\pi}{2}
Ta có : \(A=\frac{\tan\alpha}{1+\tan^2\alpha}=\tan\alpha.\cos^2\alpha=\sin\alpha.\cos\alpha=\frac{3}{5}\cos\alpha\left(1\right)\)
\(\cos^2\alpha=1-\sin^2\alpha=1-\left(\frac{3}{5}\right)^2=\frac{16}{25}\) (2)
Vì \(\alpha\in\left(\frac{\pi}{2};\pi\right)\) nên \(\cos\alpha<0\)
Do đó, từ (2) suy ra \(\cos\alpha=-\frac{4}{5}\) (3)
Thế (3) vào (1) ta được \(A=-\frac{12}{25}\)
tính
a) \(\tan^2\alpha-\sin^2\alpha-\tan^2\alpha\times\sin^2\alpha\)
b)\(\frac{sin^4\alpha-cos^4\alpha}{sin\alpha+cos\alpha}-sin\alpha+cos\alpha\)